ADVANCING ASEAN HUMAN RIGHTS NORMS THROUGH EXTERNAL RELATIONS: CAPACITY, ADVANTAGES, AND THE POTENTIAL FOR EXTERNAL INTERFERENCE - Arsika, I Made Budi (UI Scholars Hub, 2016)
The gradual development of human rights norms in ASEAN has been discussed until recently. As before the human rights provisions were formally enshrined in the ASEAN Charter, many experts have shared their views on how such norms should ideally be formulated and how to use the institutional approach in the promotion and protection of human rights in Southeast Asia region.This paper mainly discusses about the role of ASEAN’s external relations to advance the ASEAN human rights norms. On the more specific topic, this paper analyzes ASEAN’s capacity to bring human rights agenda in its external relations and also analyzes the advantages that can be gained from such activities. Based on the assumption that cooperation naturally opens the room for external influences, this paper also studies whether ASEAN’s external relations on human rights issues are potential for external interference.